BALANCED NUTRITION EDUCATION AND EXPLANATION OF HOW TO BRUSH YOUR TEETH WITH PHANTOM DENTAL IN MALAYSIA - Mulyati, Danik; Huda, Mochammad Maftuchul; Setyorini, Dwi; Azizah, Siti Nur (Jurnal Pengabdian Kolaborasi dan Inovasi IPTEKS, 2024)
Balanced nutrition is when humans consume food that provides sufficient nutrition to meet the body's needs without excess or deficiency of nutrients. A balanced diet should include carbohydrates, proteins, fats, vitamins, and minerals in the right proportions according to the body's needs. By consuming a balanced diet, you can support body functions, maintain a healthy body weight, and prevent various nutrition-related diseases. If nutritional needs are met, remember to maintain proper dental health. However, most of the children of Indonesian Migrant Workers (PMI) in Malaysia experience a knowledge crisis, which results in children not caring about their nutritional intake and several times neglecting to clean their teeth properly. So, educational activities are carried out regarding balanced nutrition and how to clean teeth properly to increase children's sense of concern for their bodies with the hope that children will have better habits in the future. The learning method begins with education about balanced nutrition with lectures, followed by coloring pictures of fruits and vegetables together. After education about balanced nutrition, it continued with an explanation of how to brush your teeth properly, assisted by using a dental phantom. After the activities, the children better understood the importance of nutritional intake for the body and proper tooth-brushing techniques. This activity needs to be continued with a more creative and innovative delivery method to children to achieve the goal that PMI children in Malaysia have a high level of concern for themselves, especially in the health sector.